دور المعلمين في دعم الطلاب ذوي الاعاقة السمعية في بيئة التعلم الرقمي -من وجهة نظر المعلمين - بلبركة عبد اللطيف; بن بهلولي ادريس (جامعة الوادي - University of Eloued, 2025)
"أصبحت بيئة التعلم الرقمي ضرورة ملحّة، خاصةً للأطفال ذوي الإعاقة السمعية الذين يواجهون صعوبات في التعليم التقليدي. تناولت هذه الدراسة أهمية إدماج التعليم الرقمي لهذه الفئة، من خلال الجانب النظري الذي عرّف الإعاقة السمعية وبيئة التعلم الرقمي، وركّز على دور المعلمين في تكييف المحتوى وتقديم الدعم المناسب. ميدانيًا، تم توزيع استبيان على 130 معلمًا متخصصًا لدراسة أربعة أبعاد: التقني، الاجتماعي النفسي، التربوي الأكاديمي، والمهني التدريبي. كشفت النتائج عن دور فعّال للمعلمين في تسهيل التعلم الرقمي من خلال استخدام التكنولوجيا والدعم النفسي والتكوين المهني. خلصت الدراسة إلى أن نجاح التعليم الرقمي لهذه الفئة يعتمد بدرجة كبيرة على كفاءة المعلم واستعداده الشامل، ما يتطلب تعزيز تكوينه وتوفير الوسائل الداعمة لتحقيق تعليم دامج وفعّال. " Digital learning has become an essential necessity, especially for children with hearing impairments who face challenges in traditional education. This study highlights the importance of integrating digital education for this group by addressing both theoretical and practical aspects. The theoretical part defined hearing impairment and explored the digital learning environment, emphasizing the teacher’s role in content adaptation and providing appropriate support. In the fieldwork, a questionnaire was distributed to 130 specialized teachers to examine four dimensions: technological, psychosocial, academic-pedagogical, and professional-training. The results showed that teachers play a key role in facilitating digital learning through the use of technology, psychological support, and ongoing professional development. The study concludes that the success of digital education for students with hearing impairments largely depends on the teacher’s competence and readiness, which calls for enhanced training and support to ensure an inclusive and effective learning environment.
مذكرة ماستر قسم علم النفس وعلوم التربية تخصص تربية خاصة
Keywords: المعلمين; الاعاقة السمعية; بيئة التعلم الرقمي; Digital learning; hearing impairments